Effectiveness and Contribution of Street Lighting Tax in Pati Regency 2018-2022 - Jaya Mumpuni; Umarella, Barus (JOURNAL INTELEKTUAL, 2024)
Introduction/Objective: This study discusses the effectiveness and contribution of Street Lighting Tax (PPJ) to Pati Regency Regional Tax Revenue during the 2018–2022 period. Background of the Problem: The Street Lighting Tax shows fluctuations in its contribution to local taxes, especially during the COVID-19 pandemic. This study aims to analyze the level of effectiveness and contribution of Street Lighting Tax to Pati Regency Regional Tax Revenue. Novelty: The study provides a comprehensive evaluation that includes trends in tax effectiveness and contribution, especially with the most recent data to 2022, which has not been widely explored in the region. Research Method: The exposition method was used with a secondary data documentation approach from BPKAD Pati Regency. The analysis was carried out to calculate effectiveness and contribution using the target ratio and the realization of tax revenue. Findings/Results: The results of the study show that the effectiveness rate of the Street Lighting Tax is very high, with an average of 106.52%. However, its contribution to Regional Tax Revenue shows a downward trend from 51.03% in 2018 to 38.47% in 2022. Conclusion: Street Lighting Tax contributes significantly to Regional Tax Revenue, albeit on a downward trend. The results of this study are expected to be a reference for optimizing the management of Street Lighting Tax by local governments.